Evaluation of the cytotoxicity, apoptotic effects, and remineralization potential of recent bioceramic-based root canal sealers - Manar M. Galal; Amira Galal Ismail; Yousra Nashaat; Tamer M. Hamdy (Journal of Oral Biology and Craniofacial Research)
Background: This study is aimed at evaluating the cytotoxicity, apoptosis/necrosis, and calcium ion release of ADseal (a resin-based sealer) and two recently introduced bioceramic-based root canal sealers, which are VDW.1 seal bioceramic and Fill Root ST. Methods: The cellular responses were studied in human periodontal ligament stem cells (hPDLSCs). Four root canal sealer extracts concentrations (100 %, 50 %, 25 %, and 12.5 %) were assessed for cell viability using the cell viability MTT essay and after 24 h, 48 h, and 7 days for all concentrations. To determine the effect of materials on apoptosis and necrosis, flow cytometry analysis was used. Calcium ion release was evaluated after 14 days of storage in distilled water using optical emission spectroscopy (ICP-OES). A two-way ANOVA was used for the statistical analysis of the acquired results. Results: Fill Root ST and VDW.1 seal bioceramic showed the highest amount of cell viability compared to ADseal sealer. Moreover, Fill Root ST, followed by VDW.1 seal bioceramic, demonstrated decreased cell apoptosis and necrosis. Moreover, VDW.1 seal bioceramic showed the highest calcium ion release, followed by Fill Root ST. ADseal sealers showed the lowest calcium ion release compared to bioceramic-based root canal sealers. Conclusions: Based on the results of this study, in terms of cytotoxicity, apoptosis/necrosis, and remineralization ability, bioceramic-based root canal sealers were more biocompatible than ADseal resin-based sealers.